The Process of Handling Qurban Animals at Several Mosques in Medan - Vivi Indriani; Abdul Wahid Ritonga; Agha Zahwan Alhatama; Farah Dias Amanda; Siti Widhi Hariestrie; Desi Amalia (Talenta Publisher, 2025)
The celebration of Eid al-Adha is a very important moment for Muslims to carry out Qurban, namely animals such as cows, camels, goats, and sheep. The mosque is a place for the community to distribute Qurban animals. Therefore, it is important to observe during the process of handling Qurban livestock. The research used a purposive sampling method, the mosques selected were mosques that had more than 10 slaughtered animals. The study was conducted in five mosques in Medan. The results of the observation showed that the livestock had been fasting before the slaughtering process. The storage place for Qurban animals is still not right because it is left in an open area that is crowded with people and can cause livestock to become stressed. The process of lying down Qurban animals is still done by tying the legs and the animals are slightly slammed. The process of skinning and removing the innards is fairly good, neat and clean. However, during the meat cutting process, many shortcomings were seen. The carcass was cut on a tarpaulin that was passed and stepped on by participants or the committee, and the carcass was not withered. The process of distributing the meat was carried out as soon as possible to prevent damage or reduced quality of the meat. Socialization or training is needed for the committee or workers to improve the quality of Qurban meat